Looping upcycling SO2 into value-added H2S by fast-induced reduction process for heavy metals treatment in nonferrous smelting industry. (1st January 2023) - Sun, Xiaoming; Liu, Zhisong; Huang, Wenjun; Ji, Leipeng; Xu, Haomiao; Qu, Zan; Yan, Naiqiang
Highlights: An SO2 looping upcycling system is proposed to produce high concentration of H2 S (>20 vol%) for heavy metals treatment; The addition of H2 can efficiently enhance the activity, selectivity, and stability in SO2 and CH4 reactions; The CoMoS specie is the active site for H2 S production in the fast-IRP. Abstract: Reversing the pollution to a value-added product can simultaneously alleviate environmental problems and achieve a circular economy. In nonferrous smelting industries, SO2 is hazardous pollution that should be disposed, but H2 S is usually required for heavy metals (HMs) treatment. Herein, we developed a field SO2 looping upcycling technology for value-added H2 S production to meet the HMs treatment. Results demonstrated that the H2 could accelerate the kinetic rate and decrease the energy barriers of the SO2 and CH4 reaction by a fast-induced reduction process (fast-IRP). Thus, the H2 S production rate in fast-IRP was three times higher than the direct reaction between SO2 and CH4 . Meanwhile, the T90 temperature (690 °C) was significantly lower than SO2 and CH4 reaction about 90 °C. Fast-IRP also can resist the SO2 poison effect and prevent sulfation, enhancing the activity, long-term stability (no visible efficiency loss in 50 h), and selectivity (nearly 100 %). Integrated the characterizations and DFT results, we found that the H2 would firstly attack the uncoordinated sulfur species with a hydrodesulfurization process to form the HS - /H2 S intermediate species with a lower energy barrier (1.57 eV) than the CH4 (2.83 eV), which can facilely protect the Mo-terminated to avoid sulfation poison. Subsequently, the HS - /H2 S* species would react with the adsorbed SO2 to Sx * to support the deep-reduction reaction for H2 S production. This work proposes an actual SO2 field utilization route and also will enlighten an induced redox cycle in the sulfur reduction over the pre-sulfurized catalysts.